Georgia Country Assistance Evaluation, 1993-2007 - World Bank (Washington, DC, 2012)
Georgia's development path was highly uneven after the country gained independence in 1991. Civil war, secessionist movements, and economic crises resulted in a sharp and protracted fall in output and hyperinflation in the immediate post-independence years. In 1994-96 the country implemented a successful stabilization program, reining in hyperinflation and restoring growth. But in subsequent years the government failed to overcome problems arising notably from economic mismanagement and widespread corruption, leading to poor public services, a deepening energy crisis, and political and economic uncertainty. After the November 2003 raised revolution, the new government executed an ambitious reform program that quickly produced results: rapid economic growth, improved governance, and better living conditions. The World Bank's experience in Georgia closely followed the successes and failures of the country's development. Three distinct sub-periods can be identified, based on the timing of the Bank's country strategies, changes in government policy course, and exogenous factors: 1994-97, 1998-2003, and 2004-07. With Georgia now on the path to international Development Association (IDA) graduation and becoming eligible for International Bank for Reconstruction and Development (IBRD) borrowing, the challenge for the Bank is to sustain a strong partnership with an emerging middle-income country.